Biological Applications of the Receptor Mimetic Peptide Mastoparan - Jones, Sarah; Howl, John (Current Protein and Peptide Science, 2006)
The receptor mimetic and mast cell degranulating peptide mastoparan (MP) translocates cell membranes as an amphipathic α-helix, a feature that is undoubtedly a major determinant of bioactivity through the activation of heterotrimeric G proteins. Chimeric combinations of MP with G protein-coupled receptor (GPCR) ligands has produced peptides that exhibit biological activities distinct from their composite components. Thus, chimeric peptides such as galparan and M391 differentially modulate GTPase activity, display altered binding affinities for appropriate GPCRs and possess disparate secretory properties. MP and MP-containing chimerae also bind and modulate the activities of various other intracellular protein targets and are valuable tools to manipulate and study enzymatic activity, calcium homeostasis and apoptotic signalling pathways. In addition, charge delocalisation within the hydrophilic face of MP has produced analogues, including [Lys5, Lys8,Aib10]MP, that differentially regulate mast cell secretion and/or cytotoxicity. Finally, the identification of cell penetrant variants of MP chimerae has enabled the effective intracellular delivery of non-permeable biomolecules and presents an opportunity to target novel intracellular therapeutic loci.
Keywords: secretion